Predictive factors of extremity graft occlusion after endovascular repair of abdominal aortic aneurysm: A 13-year single center experience - Kaptaniderya Tayfur; Ferhat Borulu; Melih Urkmez; Alpaslan Telli (Turkish Journal of Vascular Surgery)
Aim: Graft leg thrombosis (GLT) after Endovascular Aortic Repair (EVAR) is an important problem affecting morbidity/mortality. In addition to anatomical factors such as aortic neck angle and diameter in graft leg thrombosis; we aimed to convey the roles of graft extension to the external iliac artery and the effect of graft type selection on the results. Material and Methods: Analysis of 512 patients who underwent EVAR between 2010 and 2023 was performed. The effects of anatomical factors, graft material, underlying diseases, age and gender on the development of graft leg thrombosis were evaluated. Anatomical measurements were evaluated in terms of their predictive power for graft leg thrombosis by Receiver Operating Characteristic (ROC) analysis. Results: The prevalence of graft leg occlusion was significantly associated with some anatomical factors, especially increased aortic neck angle (OR=1.07, p [Turk J Vasc Surg 2024; 33(3.000): 160-70]